2010
DOI: 10.1088/0022-3727/43/3/035302
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and computational study on the phase stability of Al-containing cubic transition metal nitrides

Abstract: The phase stability of Al-containing cubic transition metal (TM) nitrides, where Al substitutes for TM (i.e. TM1−x Al x N), is studied as a function of the TM valence electron concentration (VEC). X-ray diffraction and thermal analyses data of magnetron sputtered Ti1−x Al x N, V1−x Al x N and Cr1−x Al x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 82 publications
9
61
1
Order By: Relevance
“…2), in a very good agreement with the previously reported value of 0.54 obtained with a DC process employing substrate rotation and significantly shorter target-to-substrate distance. 60 The consequences of such growth conditions for the evolution of the spatially resolved chemical composition are revealed here by atom probe tomography (see Fig. 4).…”
Section: Discussionmentioning
confidence: 91%
“…2), in a very good agreement with the previously reported value of 0.54 obtained with a DC process employing substrate rotation and significantly shorter target-to-substrate distance. 60 The consequences of such growth conditions for the evolution of the spatially resolved chemical composition are revealed here by atom probe tomography (see Fig. 4).…”
Section: Discussionmentioning
confidence: 91%
“…28 The difference has been explained in terms of volume mismatch, favoring nucleation and growth, and the electronic structure as driving forces for phase separation, allowing for spinodal decomposition. [29][30][31] These decomposition mechanisms give a)…”
Section: à3mentioning
confidence: 99%
“…is chosen which has shown that they can improve CrN thermal stability as well as mechanical properties. 136,147,[162][163][164][165][166][167][168][169] Despite the fact that the mechanical properties of CrN has been well studied. The electrical properties of CrN are still controversial with conclusion varying from report to report.…”
Section: Review Of Chromium Nitride (Crn)mentioning
confidence: 99%